Direct access versioning for multidimensional database schema creation - Jarernsri L. Mitrpanont (2018)
This paper proposes a multidimensional schema management approach by focusing on the dimension version update to support the multiple versions query in OLAP application. The evolution support of the multidimensional database (MDB) is based on the schema versioning concept. We introduce the Direct Access Versioning (DAV) technique to minimize cost of schema version creation of the MDB schema appearing in data warehouse (DW) systems. The technique maintains the change of dimension data by retaining only the changed class of dimensions in a supporting dimension version (SDV) which will be available for an immediate construction of any schema version. Thus, the efficiency of schema version construction is significantly improved since no dynamic dimension instance conversion is required. © 2006 IEEE.